The challenges involved when Arab women forge a path to educational leadership: Context, personal cost, and coping. (September 2019) - Arar, Khalid Husny
This paper traces challenges faced by six Arab women from three different Arab localities – Palestinian Arab society in Israel, Palestinian Authority territories, and Jordan – on their path to appointment as school principals, investigating how they cope with the challenges involved in women's leadership in a patriarchal society. Qualitative methodology employed in-depth interviews to elucidate the life stories of six Arab women principals. Findings show that the women's professional careers were empowered by family support. They report various difficulties and obstacles that they needed to overcome, especially since they are expected to continue to fulfil their homemaker role while complying with the requirements of their demanding profession. It is concluded that Arab women who attain educational leadership posts employ their strong characteristics, their empowered agency, and the values they acquire and represent to improve their social status, transform their personal and professional identity, and improve their resources despite restrictive cultural norms. Enlisting support from their families and other resources, they overcome barriers on the path to principalship. It is recommended that government policy in the studied societies should encourage women to undertake senior roles in education and provide the necessary mentoring and support to ensure their success. Further implications of the findings are discussed.